2010
DOI: 10.1080/07900621003655668
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Planning Perspective for Measures Concerning Flood Risk Management

Abstract: As a reaction to flooding events, various governments in Europe addressed the need to create more physical space for water. Experiences in the Netherlands have shown, however, that the development and implementation of these measures can result in local opposition. Based on an examination of such conflicts, it is argued that spatial planning should not only be regarded as an instrument for regulating the land required for flood reduction, but also as an important substantive perspective through which participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 16 publications
(22 reference statements)
0
20
0
1
Order By: Relevance
“…This insight parallels the notion of collaborative planning (Healey 2007 ) that has demonstrated that increased participation with civil society has the potential to mobilize collective action to achieve strategic urban governance targets (Neuvel and van der Knaap 2010 ;Tezer 2008 ;Ernstson et al 2008 ;Colding et al 2013b ). Fig.…”
Section: Cognitive Resilience Buildingmentioning
confidence: 97%
“…This insight parallels the notion of collaborative planning (Healey 2007 ) that has demonstrated that increased participation with civil society has the potential to mobilize collective action to achieve strategic urban governance targets (Neuvel and van der Knaap 2010 ;Tezer 2008 ;Ernstson et al 2008 ;Colding et al 2013b ). Fig.…”
Section: Cognitive Resilience Buildingmentioning
confidence: 97%
“…Despite several studies concentrating on involvement issues in controversies of flood risk reduction measures (e.g. Junker et al ., ; Neuvel and Van Der Knaap, ; Rhodius, ), more research and practical knowledge is needed to elaborate how more intense, broader, earlier and continuous participation – which is asked for in the cases – could be implemented and whether this proves expedient. Concepts such as Renn's ‘Stakeholder Involvement Escalator’ (, p. 10) and related formats of participation need to be examined regarding their help to solve controversies.…”
Section: Discussionmentioning
confidence: 99%
“…Junker et al, 2007) and using more interactive and engaging formats (e.g. Neuvel and Van Der Knaap, 2010).…”
Section: Local Controversies Of Flood Risk Reduction Measures In the mentioning
confidence: 99%
See 2 more Smart Citations